2007
DOI: 10.1002/dneu.20454
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic, but not estrogenic, protection of motoneurons from somal and dendritic atrophy induced by the death of neighboring motoneurons

Abstract: Motoneuron loss is a significant medical problem, capable of causing severe movement disorders or even death. We have been investigating the effects of motoneuron loss on surviving motoneurons in a lumbar motor nucleus, the spinal nucleus of the bulbocavernosus (SNB). SNB motoneurons undergo marked dendritic and somal atrophy following the experimentally induced death of other nearby SNB motoneurons. However, treatment with testosterone at the time of lesioning attenuates this atrophy. Because testosterone can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 68 publications
(83 reference statements)
7
50
3
Order By: Relevance
“…Consistent with most other morphological effects in adult SNB motoneurons, the neuroprotective effects of steroid treatment appear to be strictly androgenic, as treatment with either T or DHT, but not EB, attenuates induced somal and dendritic atrophy following saporin injections (Fargo and Sengelaub, 2007). Thus, the SNB stands in contrast to some other areas in the nervous system, where estradiol has powerful neuroprotective effects (Henderson and Reynolds, 2002;Hoffman et al, 2006).…”
Section: Neurotherapeutic Effectssupporting
confidence: 60%
See 1 more Smart Citation
“…Consistent with most other morphological effects in adult SNB motoneurons, the neuroprotective effects of steroid treatment appear to be strictly androgenic, as treatment with either T or DHT, but not EB, attenuates induced somal and dendritic atrophy following saporin injections (Fargo and Sengelaub, 2007). Thus, the SNB stands in contrast to some other areas in the nervous system, where estradiol has powerful neuroprotective effects (Henderson and Reynolds, 2002;Hoffman et al, 2006).…”
Section: Neurotherapeutic Effectssupporting
confidence: 60%
“…Local blockade of estrogen receptors at the BC muscle of gonadally intact males results in severely reduced dendritic lengths similar to those seen in castrates, whereas local administration of estradiol to the BC muscle of castrated males supports dendritic growth. This estrogenic influence is limited to the early postnatal period: the morphology of SNB motoneurons is insensitive to estrogens after 4 weeks of age (Goldstein and Sengelaub, 1994;Hebbeler et al, 2001;Warren and Sengelaub, 2002) or in adulthood (Forger et al, 1992;Fargo and Sengelaub, 2007). The transient influence of estrogens on SNB dendritic growth is coincident with a period in which high levels of NMDA receptors are expressed in the spinal cord, and locally in the SNB nucleus (Verhovshek et al, 2005).…”
Section: Dendritic Developmentmentioning
confidence: 99%
“…normal development 24,33,34 , after changes in dendritic interactions 33 and afferent input [35][36][37] , and after injury 6,[21][22][23]38 .…”
Section: Dendritic Lengthmentioning
confidence: 99%
“…Brown, et al has shown that agonists to the androgen receptor speed up the recovery time after sciatic nerve crush [14]. Furthermore, androgen treatment in the context of peripheral neurotoxicity (using saporin) was shown to be neuroprotective [15].…”
Section: Treatment Groupsmentioning
confidence: 99%